TANTANGAN DAN PELUANG DALAM PEMBIAYAAN PENDIDIKAN STUDI KASUS DI SMPN 3 SILIRAGUNG BANYUWANGI - Kholil, Agus Afwil; Al Rosid, Moh. Harun (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
Education financing is a key factor in determining the quality of education services, but SMPN 3 Siliragung Banyuwangi faces various challenges such as limited operational budget, less than optimal utilization of BOS Funds, and limited financial management. This study aims to analyze the challenges and opportunities in education financing and explore solutions to improve financial management to support the quality of education. The results of the study indicate that budget limitations force schools to prioritize urgent needs, while BOS Funds are more focused on improving facilities than developing learning. The strategic role of the Principal in financial planning and management is quite significant, although it still faces obstacles such as limited human resources and supervision. In conclusion, although the challenges of education financing are quite large, there are opportunities to improve the effectiveness of financial management through careful planning, strict supervision, and collaboration with external parties, so that they can optimize existing funds and support sustainable improvements in the quality of education